West Bank and Gaza - Assessment of Restrictions on Palestinian Water Sector Development - World Bank (World Bank, 2012)
The goal of the assessment is to develop a balanced analysis and create awareness of the factors restricting Palestinian water sector development as well as of the economic, social, and environmental impacts of these restrictions. The assessment addresses factors such as sector governance, and movement and access (M&A) restrictions beyond the control of the Palestinian Authority, as well as internal contributing factors, notably governance and capacity weaknesses of Palestinian institutions. This report, examines in turn: (1) the current situation, progress and impacts since Oslo; (2) the principal problems of the Palestinian water sector; and (3) the underlying constraints and their relation to the overall governance environment established under Oslo and to other institutional aspects. A fourth and final section looks at the agenda that faces the Palestinian authority in trying to develop water resources and services as a means to improve living standards and to increase economic growth.